Demonstrating Intertumoural Differences in Vascular-Metabolic Phenotype with Dynamic Contrast-Enhanced CT-PET. (26th April 2011) - Miles, K. A.; Williams, R. E.; Yu, D.; Griffiths, M. R.
Abstract : Purpose . To assess whether the differences in vascular-metabolic relationships between lymphoma masses and colorectal liver metastases predicted from previous histopathological studies can be demonstrated by dynamic contrast-enhanced CT (DCE-CT) combined with fluorodeoxyglucose positron emission tomography (FDG-PET). Methods . DCE-CT and FDG-PET studies were drawn from an imaging archive for patients with either lymphoma masses (n = 11 ) or hepatic metastases from colorectal cancer (CRM: n = 12 ). Tumour vascularity was assessed using DCE-CT measurements of perfusion. Tumour glucose metabolism was expressed as the mean FDG Standardised Uptake Value (SUV FDG ). The relationship between metabolism and vascularity in each group was assessed from SUV FDG /perfusion ratios and Pearson correlation coefficients. Results . An SUV FDG threshold of 3.0 was used to designate lymphoma masses as active (AL, n = 6 ) or inactive lymphoma (IL, n = 5 ). Tumour perfusion was significantly higher in AL (0.65 mL/min/mL) than CRM (0.37 mL/min/mL: P = .031 ) despite similar SUV FDG (5.05 and 5.33, resp.). AL demonstrated higher perfusion values than IL (0.24 mL/min/mL: P = .006 ). SUV FDG /perfusion was significantly higher in CRM (15.3 min) than IL (4.2 min, P < .01 ). There was no correlation between SUV FDG and perfusion for any patient group.